2001
DOI: 10.1128/jcm.39.10.3537-3540.2001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative, Fluorogenic Probe PCR Assay for Detection of Human Herpesvirus 8 DNA in Clinical Specimens

Abstract: A quantitative, fluorescence-based PCR assay (TaqMan-based system) was developed for detection of human herpesvirus 8 (HHV-8) DNA in clinical specimens. Primers and probes chosen from each of five 10-kb segments from the unique region of the HHV-8 genome were evaluated for sensitivity with dilution series of DNA extracted from a cell line (BCBL-1) that harbors HHV-8 DNA. Although several of the primer-probe sets performed similarly with BCBL-1 DNA that had been diluted in water, their performance differed when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Studies of three different populations with high STD and AIDS prevalences in San Francisco agree with this behavioral risk factor, suggesting that insertive oral sex may be the highest risk behavior, as inferred from the easy detection of KSHV in saliva but a low viral load in semen (386). In agreement, many studies have found KSHV in the saliva of seropositive patients (45,266,392,481,513), and KSHV has been detected in prostate tissue and the male urogenital tract (132,348,481,483); detection of KSHV in the ejaculate has been reported but remains controversial (255,300,348,396,481; P. Gupta, M. K. Singh, C. Rinaldo, M. Ding, H. Farzadegan, A. Saah, D. Hoover, P. Moore, and L. Kingsley, Letter, AIDS 10:1596-1598, 1996). Taken together, these studies affirm a route of sexual transmission for KSHV that differs significantly from that for HIV-1.…”
Section: Aids-associated Kssupporting
confidence: 67%
See 1 more Smart Citation
“…Studies of three different populations with high STD and AIDS prevalences in San Francisco agree with this behavioral risk factor, suggesting that insertive oral sex may be the highest risk behavior, as inferred from the easy detection of KSHV in saliva but a low viral load in semen (386). In agreement, many studies have found KSHV in the saliva of seropositive patients (45,266,392,481,513), and KSHV has been detected in prostate tissue and the male urogenital tract (132,348,481,483); detection of KSHV in the ejaculate has been reported but remains controversial (255,300,348,396,481; P. Gupta, M. K. Singh, C. Rinaldo, M. Ding, H. Farzadegan, A. Saah, D. Hoover, P. Moore, and L. Kingsley, Letter, AIDS 10:1596-1598, 1996). Taken together, these studies affirm a route of sexual transmission for KSHV that differs significantly from that for HIV-1.…”
Section: Aids-associated Kssupporting
confidence: 67%
“…Active KSHV replication and increased detection by PCR of viral DNA in the peripheral blood are strongly correlated with (i) increased risk of progression to KS (13,530) and (ii) increased severity of pathogenic stage of KS (47,68); the peripheral viral load predicts the pathogenic outcome of the infection (410). KSHV has also been found in the neutrophil subset of PBMCs (285) (481).…”
Section: Histopathogenesis Of Ks and Its Relationship To Kshv Infectionmentioning
confidence: 99%
“…Reagents and enzymes used for TaqMan PCR were obtained from PE Applied Biosystems (Foster City, Calif.). The sequences for the TaqMan FAM probe and ORF37 primers used for the quantitative detection of KSHV molecules were published previously (52) and are listed in Table 1. Each 25-l PCR mixture contained TaqMan universal PCR master mix and 0.25 l of 20 M primer stock for both forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%
“…To better quantify the amount of virus produced by transfection of 293 cells, a real-time PCR assay targeting the ORF37 gene was used essentially as described previously (52). The relative amounts of BAC36 DNA and BAC36⌬K8.1 DNA found in supernatants of transfected 293 cells were obtained from a standard curve based on known amounts of BAC36 DNA (see Materials and Methods).…”
mentioning
confidence: 99%
“…A duplex quantitative Taqman PCR system was optimized for HHV-8 orf37 and cellular RNase P. The PCR primers and 6-carboxyfluorescein (FAM)-labeled probe used to quantify orf37 have been described previously (32), but a Black Hole Quencher (BHQ1; Biosearch Technologies, Novato, Calif.) was used instead of 6-carboxytetramethylrhodamine (TAMRA). The forward and reverse primers used for RNase P amplification (kindly provided by Karen McCaustland and Brian Holloway) were 5Ј-AGATTTGGACCTGCGAG CG-3Ј and 5Ј-GAGCGGCTGTCTCCACAAGT-3Ј, respectively; the probe was 5Ј-TTCTGACCTGAAGGCTCTGCGCG-3Ј, labeled at the 5Ј end with 6-carboxy-4,5-dichloro-2,7-dimethoxyfluorescein (JOE) and at the 3Ј end with BHQ.…”
Section: Methodsmentioning
confidence: 99%